Optical Fiber Communication Conference and Exhibit 2002
DOI: 10.1109/ofc.2002.1036385
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-wave pumped holey fiber Raman laser

Abstract: Wavelength (om)WR5 Fig. 2. Measured optical SNRs and Q factors of optical carriers 100 nm) and is realized when nonlinear materials, such as optical fibers, are pumped bypicosecond optical pulses. It occurs due to the combined effects of self-phase modulation, cross-phase modulation, and parametric four-wave mixing. It isnoteworthythatthegeneratedSClight has high coherence and high SNR. Optical carriers are obtained by spectrally slicing individual longitudinal modes from the SC spectrum. Therefore, multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…For example, poled HF devices based on second order effects should be possible with conversion efficiencies and operating bandwidth two orders of magnitude greater than can be achieved with standard fibres [47]. Similarly, it should be possible to make HF Raman and Brillouin devices with greatly reduced operating powers or device lengths and indeed first experiments in this area have been performed [46,48,49].…”
Section: Device Applicationsmentioning
confidence: 99%
“…For example, poled HF devices based on second order effects should be possible with conversion efficiencies and operating bandwidth two orders of magnitude greater than can be achieved with standard fibres [47]. Similarly, it should be possible to make HF Raman and Brillouin devices with greatly reduced operating powers or device lengths and indeed first experiments in this area have been performed [46,48,49].…”
Section: Device Applicationsmentioning
confidence: 99%
“…It has been already shown that photonic-crystal fibers (PCFs), compared with conventional single mode fibers, can be designed very flexibly to enhance nonlinear effects, by proper choice of the lattice parameters, that is the center-to-center air-hole spacing, or pitch , and the ratio between hole diameter and pitch. Theoretical studies have recently been performed on highly nonlinear holey fibers [3] and germania-doped triangular PCFs [4], while experimental demonstrations include continuous-wave pumped Raman lasers [5] and -band RAs [3], showing the potential of PCFs in obtaining high Raman gain efficiency.…”
Section: Introductionmentioning
confidence: 99%